Kiss of the spider woman [videorecording (Blu-Ray)] - Schrader, Leonard; Hurt, William; Julia, Raul; Braga, Sonia, 1950-; Lewgoy, José; Gonçalves, Milton, 1933-2022; Maia, Nuno Leal, 1947-; Pires, Myriam, 1927-2004; Puig, Manuel (Criterion collection, 2026)
The story of two radically different men imprisoned together under the Brazilian military dictatorship. One is Valentin, a journalist being tortured for his political beliefs. The other is Molina, a gay window-dresser who fills their lonely nights by spinning romantic fantasies drawn from memories of old movies.